I used The Euclidean formula and the extended euclidean formula as well but the working went for ever. Maybe I will give it another go. I thought myabe our guest knew what s/he was talking about and might explain it simply. ://
I'm not so sure I follow what you did either I will have to study it ://
I don't understandwhat I'm doing wrong. What does the (a) stand for in the function
\( f(a) = 3a – a^2\)
a is a variable and can be equal to any number or any mathematical expression.
It is the same as
\(f(x) = 3x – x^2\\ f(x) = – x^2+3x\\ f(x) =-x(x-3) \)
This would graph as a concave down parabola with roots of 0 and 3
Mmm seems to be some disagreement here ://
Bill, Phil, and Jenny are siblings.
Bill is twice as old as Phil. 2P=B
Jenny is two years younger than Bill. B-2=J B=J+2
Currently, their dad is twice as old as the sum of their ages. D=2(P+B+J)
In nine years, Dad's new age will be equal to the sum of his three kids' new ages.
therefore Dad is 36
P=4 Phil is 4
Bill is 8
Jenny is 6
Bill 8, Phil 4 , and Jenny 6 are siblings. Dad is 36
Bill is twice as old as Phil. yes
Jenny is two years younger than Bill. yes
Currently, their dad is twice as old as the sum of their ages. 2*(8+4+6)=36 yes
In nine years, Dad's new age will be equal to the sum of his three kids' new ages. What is Jenny's current age? 45=18+27 yes